1996
DOI: 10.1007/bf01276422
|View full text |Cite
|
Sign up to set email alerts
|

Platelet phenolsulphotransferase activity, monoamine oxidase activity and peripheral-type benzodiazepine binding in demented patients

Abstract: Blood platelet phenolsulphotransferase and monoamine oxidase activities, as well as platelet peripheral-type benzodiazepine binding have been studied in several neuropsychiatric disorders, in order to identify biochemical markers for altered brain functioning. In the present work, we determined platelet phenolsulphotransferase and monoamine oxidase activities in demented patients: they showed significantly higher phenolsulphotransferase and monoamine oxidase activities than controls. A significant positive cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The results indicate that more severe AD symptoms are associated with reduced platelet 5-HT concentration and lower platelet MAO-B activity. The mild but significant positive correlation between MMSE scores and platelet MAO-B activity is in line with the association between enzyme activity and severity of AD (Bongioanni et al 1996). MMSE scores, indicating severity of dementia, were significantly negatively correlated with age in both control subjects and patients with AD, indicating decline in cognitive functions associated with aging.…”
Section: Discussionsupporting
confidence: 77%
“…The results indicate that more severe AD symptoms are associated with reduced platelet 5-HT concentration and lower platelet MAO-B activity. The mild but significant positive correlation between MMSE scores and platelet MAO-B activity is in line with the association between enzyme activity and severity of AD (Bongioanni et al 1996). MMSE scores, indicating severity of dementia, were significantly negatively correlated with age in both control subjects and patients with AD, indicating decline in cognitive functions associated with aging.…”
Section: Discussionsupporting
confidence: 77%
“…One hypothesis is that the Sult1A1 enzyme might be involved in vascular damage in the genesis of dementia with vascular contributions. It has previously been found that platelet sulfotransferase activity was higher in AD compared with controls [32] . Another study indicated a possible association of this group of enzymes and protection against cell damage during aging [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The Sult1A1 consists of at least four different subfamilies of enzymes [31] . A previous study found that platelet sulfotransferase activity was signifi cantly higher in dementia of Alzheimer type compared with controls and that the increased activity was positively correlated with the severity of dementia [32] .…”
Section: Introductionmentioning
confidence: 99%
“…Several other biological systems have been studied in platelets of AD patients, such as e.g. decreased plasma antioxidant power levels [107], decreased cathepsin D [141], increased platelet glutamine synthetase-like protein level in MCI [112], increased NA,K-ATPase activities in AD [107], unchanged Vitamin E and cholesterol content between AD and controls [32] or increased phenolsulphotransferase activity in demented patients [142] or decreased platelet peripheral-type benzodiazepine binding [143]. However, we do not claim to provide a complete overview of all markers.…”
Section: Overview Of Other Platelet Components Found To Be Altered In Admentioning
confidence: 99%